2004
DOI: 10.1063/1.1809267
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen nonstoichiometry and dielectric evolution of BaTiO3. Part I—improvement of insulation resistance with reoxidation

Abstract: Impedance spectroscopy, transmission electron microscopy, and electron energy-loss spectroscopy are used to correlate local electrical properties with the microstructure and microchemistry of BaTiO 3 in Ni-electrode multilayer ceramic capacitors. High densities of linear defects and some grains with structural modulations are observed in BaTiO 3 grains in the as-cofired capacitors. The modulated structure is formed on {111} planes of the BaTiO 3. Both types of structural defects are associated with high concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
180
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(191 citation statements)
references
References 31 publications
11
180
0
Order By: Relevance
“…Because of this, a capacitive device of higher performance is obtained by higher resistivity. 25 Figure 5 illustrates that resistivity is very similar among the four BNT-BT-KNN materials from 100 to 400°C.…”
Section: Figmentioning
confidence: 97%
“…Because of this, a capacitive device of higher performance is obtained by higher resistivity. 25 Figure 5 illustrates that resistivity is very similar among the four BNT-BT-KNN materials from 100 to 400°C.…”
Section: Figmentioning
confidence: 97%
“…Therefore, alloying is thermodynamically possible if BaTiO 3 undergoes significant reduction [16][17][18][19]. In fact, we recently identified the formation of discrete interfacial alloy layers consisting of Ni, Ba and Ti with a thickness of 5-15 nm between Ni electrodes and BaTiO 3 in commercial MLCCs [16][17][18][19]. The appearance of this alloy was attributed to the local reduction of the BaTiO 3 by residual carbon remaining from the binder burnout process.…”
Section: Introductionmentioning
confidence: 96%
“…The p-type BaTiO 3 -Ni interface will have a hole accumulation and would show an ohmic contact [14]. Previous studies of BME-MLCC chips before and after the reoxidation treatment confirmed the formation of blocking Schottky barrier in either case [3,5]. This means that the BaTiO 3 -based dielectric is still n-type semiconducting even after the reoxidation treatment and different from the airfired cases.…”
Section: Introductionmentioning
confidence: 52%
“…One of the current issues in state-of-the-art base-metal electrode multilayer ceramic capacitors (BME MLCCs) with dielectric and electrode layer thicknesses around or below 1 μm is the discontinuity of Ni electrodes, which can affect the electrical performance and reliability of final products [1,2]. Recently, our investigations revealed the formation of an interfacial low-melting point (Ni,Ba,Ti) alloy with a melting point as low as 1000-1150°C at Ni-BaTiO 3 interfaces [3][4][5][6]. The reduction process to produce the metallic Ti and Ba components results from the presence of residual carbon content from the organics used in the tape casting and screen printing process steps.…”
Section: Introductionmentioning
confidence: 99%